HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KEPATUHAN KLIEN DIABETES MELITUS DALAM MENJALANI DIET DI RUANG RAWATAN PENYAKIT DALAM RUMAH SAKIT AISYIYAH PARIAMAN TAHUN 2022 - Asmiati, Asmiati (Ensiklopedia of Journal, 2022)
Diabetes mellitus is referred to as the Mother of Disease because Diabetes mellitus is the mother of various diseases. In Kota Pariaman, to be precise, Aisyiyah Pariaman Hospital, it was recorded that in 2021 there were 1,738 DM cases. Routine control compliance is an aspect in the management of Diabetes mellitus. One of the factors that can affect adherence to routine control is the knowledge and support from families of people with DM. This type of research uses quantitative descriptive analytical design with a Cross Sectional Study approach. The study was conducted on April 23 to May 25, 2022. The study sample was 95 patients' families. Sampling by accidential sampling. Statistical test using Chi Square. The results showed that most of the respondents (52.6%) had low knowledge about the DM diet; Most of the respondents (54.7%) had less family support in giving DM diet; Most of the respondents (55.8%) did not comply with the DM diet at the Aisyiyah Pariaman Hospital. There is a significant relationship between knowledge and family support with adherence to the DM diet at Aisyiyah Pariaman Hospital. It is hoped that DM patients can apply a healthy lifestyle with a balanced diet, adhere to the diet provided and be more active in participating in any counseling about DM given by health workers.Keywords  : Knowledge, family support and Diabetes Melitus